Effects of a new herbicide (Aminocyclopyrachlor) on buffalograss and forbs in shortgrass prairie - Harmoney, Keith R.; Stahlman, Phillip W.; Geier, Patrick W.; Rupp, Robert (My University, 2013)
Herbicides used to control many forb species in pastures may injure desirable native grass species. Buffalograss, a major component of shortgrass rangeland, often is injured by some growth regulator herbicides, such as 2,4-D and dicamba. Aminocyclopyrachlor (formerly known as DPX-MAT28 and herein termed ACPCR), a new synthetic auxin herbicide chemistry for control of broadleaf weeds, was investigated for injury to buffalograss and control of forbs in shortgrass prairie at varying rates of application. In the season of application, ACPCR at rates of 140 g ai haˉ¹ or less caused buffalograss injury that was either negligible or short-lived, and visual estimates of grass injury were 8% or less at the end of the growing season. At ACPCR rates of 280 g haˉ¹, more injury was evident at 3 wk after treatment (WAT) than at the end of the season if adequate precipitation was available for new leaf growth. When precipitation was lacking, evidence of injury persisted through to the end of the season when treated at the greatest rate of ACPCR. Buffalograss injury was mainly in the form of browned leaf tips, but total buffalograss dry matter yield was not different between any treatments in either year. The year after treatment, no buffalograss injury was evident from any of the herbicide rates. Final forb control was 97% or greater each year for ACPCR at the 140 and 280 g haˉ¹ rates. In this experiment, rates as low as ACPCR at 140 g haˉ¹ provided excellent forb control and maintained buffalograss productivity.
Keywords: Dry matter yield; Injury; Rangeland; Buffalograss; Forbs